Boosting sustainable agriculture by arbuscular mycorrhizal fungi under abiotic stress condition - Noor Alam Chowdhary; L.S. Songachan (Plant Stress)
Global climate change presents a major threat to agroecosystems, intensifying abiotic stresses such as drought, salinity, heavy metal toxicity, and temperature extremes that hamper plant productivity and food security. Addressing these challenges requires the implementation of sustainable, eco-friendly strategies. Arbuscular mycorrhizal fungi (AMF) which form symbiotic associations with the roots of most terrestrial plants, have emerged as key biological agents to enhance plant resilience under abiotic stress conditions by improving nutrient and water uptake, modulating hormonal signalling, enhancing antioxidant defense mechanisms, and maintaining osmotic homeostasis. These mycorrhizal interactions result in improved photosynthetic efficiency, growth performance, secondary metabolites accumulation, and yield. Additionally, AMF contribute to soil health, by enhancing structure, nutrient cycling, and carbon sequestration-key components of sustainable agriculture. This review highlights the role of AMF in mitigating abiotic stress through integrative physiological, biochemical and molecular mechanisms with emphasis on staple crops along with economically and medicinally important plants. These finding underscore the broader potential of AMF in supporting resilient and sustainable agroecosystems in stress-prone environments.